Low-normal FMR1 CGG repeat length: phenotypic associations - Mailick, Marsha R.; Hong, Jinkuk; Rathouz, Paul; Baker, Mei W.; Greenberg, Jan S.; Smith, Leann; Maenner, Matthew (Frontiers in Genetics, 2014)
This population-based study investigates genotype-phenotype correlations of “low-normal” CGG repeats in the fragile X mental retardation 1 (FMR1) gene. FMR1 plays an important role in brain development and function, and encodes FMRP (fragile X mental retardation protein), an RNA-binding protein that regulates protein synthesis impacting activity-dependent synaptic development and plasticity. Most past research has focused on CGG premutation expansions (41 to 200 CGG repeats) and on fragile X syndrome (200+ CGG repeats), with considerably less attention on the other end of the spectrum of CGG repeats. Using existing data, older adults with 23 or fewer CGG repeats (2 SDs below the mean) were compared with age-peers who have normal numbers of CGGs (24-40) with respect to cognition, mental health, cancer, and having children with disabilities. Men (n = 341 with an allele in the low-normal range) and women (n = 46 with two low-normal alleles) had significantly more difficulty with their memory and ability to solve day to day problems. Women with both FMR1 alleles in the low-normal category had significantly elevated odds of feeling that they need to drink more to get the same effect as in the past. These women also had two and one-half times the odds of having had breast cancer and four times the odds of uterine cancer. Men and women with low-normal CGGs had higher odds of having a child with a disability, either a developmental disability or a mental health condition. These findings are in line with the hypothesis that there is a need for tight neuronal homeostatic control mechanisms for optimal cognitive and behavioral functioning, and more generally that low numbers as well as high numbers of CGG repeats may be problematic for health.